The effect of pelvic floor muscles training, bladder exercises and lifestyle modification on urinary incontinence in elderly men - Hossein Jafarizadeh; Zahra Maghsoudi; Farideh Namadi; Yousef Mohammadpour; Yaser Moradi (Society of Diabetic Nephropathy Prevention, 2022)
Introduction: Urinary incontinence is one of the causes of the dependence of the elderly on others and is one of the main reasons for sending the elderly to care centers. Objectives: The aim of this study was to determine the effect of behavioral interventions program on urinary incontinence in the elderly. Patients and Methods: In this quasi-experimental clinical trial (without a control group), 30 elderly men with acute urinary incontinence were selected from elderly care centers in Urmia city using the available sampling method. The intervention included pelvic floor and bladder exercises and lifestyle modification training, individually. The standard ICIQ-SF questionnaire was completed before and after the intervention. The data were analyzed by paired t-test and Wilcoxon tests. Results: The findings showed a statistically significant difference between urinary leakage frequency (P= 0.002), urinary leakage rate (P=0.001) and the effect of urinary leakage on the quality of life (P < 0.001) of the subjects before and after the intervention. Conclusion: The results of this study showed that a combination of the pelvic floor and bladder exercises and lifestyle change are effective in decreasing urinary incontinence in elderly men. Trial Registration: The trial protocol was registered in the Iranian Registry of Clinical Trials (identifier: IRCT20180808040742N2; https://en.irct.ir/trial/43204, ethical code #IR.UMSU.REC.1391.31).